Writing Death - Fernando, Jeremy (punctum books, 2011)
Writing Death opens a meditation on the possibility of mourning; of whether there is a subject, or even object, that one mourns-of whether one is mourning, can only mourn, the very impossibility of mourning itself. The manuscript is framed by two attempts at mourning-Avital Ronell's "The Tactlessness of an Unending Fadeout" and Jeremy Fernando's "adieu." In-between-for this is where both pieces posit the possibility of attending to the passing, the memory, the fading of the person-is an attempt to think this impossibility. The text is continually haunted by the question of whether one is mourning the person as such, or a particular version of the person, a reading of the person. And in reading another, in attempting to respond to the other, one can never have the metaphysical comfort that one is reading accurately, correctly; in fact, one may always already be re-writing the person. Thus, all one can do is attempt to mourn the name of that person, whilst never being certain of whether her name even refers to her any longer. All one can do is write death.